Transcriptomic Analyses for Identification and Prioritization of Genes Associated With Alzheimer’s Disease in Humans - Shi, Yuchen; Liu, Hui; Yang, Changbo; Xu, Kang; Cai, Yangyang; Wang, Zhao; Zhao, Zheng; Shao, Tingting; Li, Yixue (Frontiers in Bioengineering and Biotechnology, 2020)
Long non-coding RNAs (lncRNAs), as important ncRNA regulators, play crucial roles in the regulation of various biological processes, and their aberrant expression is related to the occurrence and development of diseases, which is gradually validated by more and more studies. Alzheimer's disease (AD) is a chronic neurodegenerative disease that often develops slowly and gradually deteriorates over time. However, which functions the lncRNAs performed in AD are almost unknown. In this study, we performed the transcriptome analysis in AD, containing 12892 known-lncRNAs, and 19053 protein-coding genes (PCGs). Further, 14 down-regulated and 39 up-regulated lncRNAs were identified, comparing with normal brain samples, which indicated that these lncRNAs might play critical roles in the pathogenesis of AD. In addition, 19 down-regulated and 28 up-regulated PCGs are also detected. Using the differentially expressed lncRNAs and PCGs through WGCNA method , a lncRNA-mRNA co-expressed network was constructed. The results were shown that lncRNAs RP3-522J7, MIR3180-2 and MIR3180-3 were frequently co-expressed with known AD risk PCGs. Interestingly, PCGs in the network are significantly enriched in brain or AD related biological functions, including brain renin-angiotensin system, cell adhesion, neuroprotective role of THOP1 in Alzheimer's disease and so on. Furthermore, it was shown that 18 lncRNAs and 7 PCGs were high expressed in normal brain tissue relative to other normal tissue types, suggesting their potential as diagnostic markers of AD, especially RP3-522J7, MIR3180-2, MIR3180-3 and CTA-929C8. In total, our study identified a compendium of AD-related dysregulated lncRNAs, and characterized the corresponding biological functions of these lncRNAs in AD, which will be helpful to understand the molecular basis and pathogenesis for AD.